A Combinational Effect of "Bulk" and "Surface" Shape‐Memory Transitions on the Regulation of Cell Alignment. Issue 9 (7th February 2017) - Uto, Koichiro; Aoyagi, Takao; DeForest, Cole A.; Hoffman, Allan S.; Ebara, Mitsuhiro
Abstract : A novel shape‐memory cell culture platform has been designed that is capable of simultaneously tuning surface topography and dimensionality to manipulate cell alignment. By crosslinking poly(ε‐caprolactone) (PCL) macromonomers of precisely designed nanoarchitectures, a shape‐memory PCL with switching temperature near body temperature is successfully prepared. The temporary strain‐fixed PCLs are prepared by processing through heating, stretching, and cooling about the switching temperature. Temporary nanowrinkles are also formed spontaneously during the strain‐fixing process with magnitudes that are dependent on the applied strain. The surface features completely transform from wrinkled to smooth upon shape‐memory activation over a narrow temperature range. Shape‐memory activation also triggers dimensional deformation in an initial fixed strain‐dependent manner. A dynamic cell‐orienting study demonstrates that surface topographical changes play a dominant role in cell alignment for samples with lower fixed strain, while dimensional changes play a dominant role in cell alignment for samples with higher fixed strain. The proposed shape‐memory cell culture platform will become a powerful tool to investigate the effects of spatiotemporally presented mechanostructural stimuli on cell fate. Abstract : Shape‐memory cell culture platform with simultaneous tunable surface topography, dimension, and network mechanics is developed to dynamically manipulate cell alignment using crosslinked poly(ε‐caprolactone). The different effects of surface topography and bulk dimension on adhered cell alignment are observed before and after shape‐memory activation.